Design and development of boiler tube outer surface inspection robot - Abdullah Ahmad Muslim (2023)
More than 80% of unscheduled boiler shutdown is due to boiler tube failure. Regular inspection of the boiler tubes is important to ensure the safety of the workplace and to avoid shutdowns. Manual inspection by a human inspector can be challenging, dangerous, tedious and at time unreliable due to human factor.